2013
DOI: 10.1016/j.bbi.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-fluorouracil chemotherapy on fatigue: Role of MCP-1

Abstract: Chemotherapy has been known to cause severe side effects, including fatigue. While the mechanisms for chemotherapy induced fatigue (CIF) are likely to be multi-factorial in origin, it is thought that inflammation and anemia may play a role. The purpose of this study was to examine the effect of chemotherapy on fatigue in mice, and further, to begin to determine if inflammation and anemia may contribute to this response. For experiment 1, C57BL/6 mice were assigned to: vehicle (PBS), low (20 mg/kg), medium (40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…We showed previously that CAF increases MCP-1 levels in WT mice (Smith et al, 2014). In addition, Mahoney et al (2013) used MCP-1-deficient mice to show that a 5-FU-mediated decline in VWRA was MCP-1 dependent (Mahoney et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…We showed previously that CAF increases MCP-1 levels in WT mice (Smith et al, 2014). In addition, Mahoney et al (2013) used MCP-1-deficient mice to show that a 5-FU-mediated decline in VWRA was MCP-1 dependent (Mahoney et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 was measured in the plasma at baseline and at 5 days and 14 days post 5-FU. Previous work in this area has shown that increased levels of MCP-1 in the plasma are associated with fatigue following 5-FU chemotherapy 13 as well as other cytotoxic chemotherapies. 14 Likewise, MCP-1, in conjunction with other inflammatory cytokines, has been associated with increased fatigue in other chronic conditions including fibromyalgia 27 and chronic fatigue syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we have reported that MCP-1-deficient mice have a heightened recovery from CIF as measured by voluntary wheel running activity. 13 There is also evidence that a diminished production of blood cells following chemotherapy treatment may contribute to CIF. In fact, a decrease in red blood cell production, leading to anemia, has been identified by the National Comprehensive Cancer Network as one of the treatable factors of CIF.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous mouse models have been developed and used to recapitulate and better understand CRF produced by various causes, including chemotherapy [17–19], radiation [20], and cancer and cancer cachexia [2123]. Given the many causes of CRF and the possibility that the underlying mechanisms of CRF may vary depending on the cause, it is important to determine if TAL has anti-fatigue effects in multiple models of CRF.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the current study used three mouse models of CRF. The first was a model of chemotherapy-induced fatigue, adapted from a published model [19]. The second was a mouse model of peripheral irradiation that causes fatigue-like behavior by mimicking the peripheral radiation exposure of radiation therapy [20].…”
Section: Introductionmentioning
confidence: 99%